The Quality of Electronic Student Worksheets Based on Critical Thinking Skills on the Concept of Biodiversity at High School Level - Nida Lessy; Muhammad Zaini; Kaspul Kaspul (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
21st-century education demands the critical thinking skills of students. Education is also required to create a generation that is skilled at using technology. Electronic Student Worksheets (LKPD) is innovative learning tools to make it easier for students in the learning process. This study aims to describe the practicality and effectiveness of electronic LKPD expectations on the concept of Biodiversity. The research method used Tessmer's Formative Evaluation design, through stages 1) expert review; 2) one-to-one evaluation; and 3) small group evaluation. The validator was 3 experts, the individual test subjects were 3 high school class X students and the small group test subjects were 4 high school class X students. Data obtained from the research instrument in the form of an assessmet sheet of practicality and effectiveness of expectations. The results of the research on the practicality of expectations have a very good category based on the responses of students and the effectiveness of expectations has a very good category (including interpretation, analysis, evaluation, inference, and explanation skills) and a good category (including self-regulation skills) based on the assessment of students' critical thinking skills.AbstrakPendidikan abad ke-21 menuntut keterampilan berpikir kritis peserta didik. Pendidikan juga dituntut menciptakan generasi yang terampil menggunakan teknologi. Lembar Kerja Peserta Didik elektronik merupakan inovasi perangkat pembelajaran untuk mempermudah peserta didik dalam proses belajar. Penelitian ini bertujuan untuk mendeskripsikan kepraktisan dan keefektifan harapan LKPD elektronik pada konsep Keanekaragaman Hayati. Metode penelitian menggunakan desain Evaluasi Formatif Tessmer, melalui tahapan 1) expert review; 2) one-to-one evaluation; dan 3) small group evaluation. Validator adalah 3 orang ahli, subjek uji perorangan adalah 3 orang peserta didik kelas X SMA dan subjek uji kelompok kecil adalah 4 orang peserta didik kelas X SMA. Data diperoleh dari instrumen penelitian berupa lembar penilaian kepraktisan dan keefektifan harapan. Hasil penelitian kepraktisan harapan memiliki kategori sangat baik berdasarkan respon peserta didik dan keefektifan harapan memiliki kategori sangat baik (meliputi keterampilan interpretasi, analisis, evaluasi, inferensi, dan eksplanasi) dan kategori baik (meliputi keterampilan pengaturan diri) berdasarkan penilaian keterampilan berpikir kritis peserta didik.